Ways of improving the economic security of fuel and energy complex enterprises - K. O. Ternavshchenko; B. A. Savv (Вестник университета, 2023)
The purpose of the article is to develop measures aimed at improving the economic security of an organization. The relevance of the chosen topic is high due to the fact that the process of successful operation and economic development of fuel and energy complex enterprises largely depends on the improvement of their financial and economic activities as well as activities in the field of security. The article analyzes the essence of the fuel and energy complex and its impact on the country’s economy. An author’s method for assessing the economic security of an enterprise carrying out its activities in the aforementioned field has been studied. Analysis of the economic security of an oil industry enterprise in 2021 was carried out. The main threats that such organizations face as well as priority ways to reduce them have been identified. The economic effect of the measures proposed to improve the economic security will presumably amount to 2 918 720.7 million rubles.